Identification of biomarkers of colitis to monitor effects of dietary omega-3 polyunsaturated fatty acids in the interleukin-10 gene-deficient mouse model of inflammatory bowel diseases : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Nutritional Science at Massey University, Manawatū, New Zealand - Berger, Nadja (Massey University, 2016)
Inflammatory bowel diseases (IBD) are characterised by chronic inflammation of the gastrointestinal tract including the colon (colitis). Increased dietary intake of salmon, which is rich in eicosapentaenoic acid (EPA), was well tolerated by IBD patients, leading to a perceived decrease in symptoms. However, better knowledge of the mechanisms by which EPA-rich diets affect IBD severity, and appropriate biomarkers for assessing these effects, are needed for potential targeted nutritional interventions. This dissertation aimed to determine the temporal effects (early (9 weeks of age) vs. established (12 weeks)) of a diet containing 3.7% EPA, and the dose-dependent effects (15% to 45%) of a salmon diet at 12 weeks of age, on the severity of colitis. Molecular responses in colon and/or liver of the interleukin-10 gene-deficient (Il10-/-) mouse model of IBD and healthy mice were assessed. Caecum digesta, urine and blood were mined to identify biomarkers (microbiota, metabolites and genes) of these responses. The EPA diet reduced the severity of colitis only in 12-week-old Il10-/- mice. This response was associated with changes in gene expression associated with lymphocyte function, eicosanoid signalling and peroxisome proliferator-activated receptor gamma signalling. The blood immune cell gene expression profile did not correlate with reduced colitis in these mice, but the urine metabolite profile was related to changes in colonic tryptophan metabolism. The effects of the salmon diets on colitis were dose-dependent in 12-week-old Il10-/- mice. The intermediate amount of salmon (30%) reduced the severity of colitis and lymphocyte-related gene expression, while enhancing genes in metabolic pathways. Tryptophan metabolism was not affected in these mice, but the urinary metabolite profile correlated with effects on hepatic tocopherol metabolism, as shown by reduced abundance of gamma-carboxyethylhydroxychroman glucoside. The abundances of V. akkermansia, Eubacterium spp., and an unclassified Rikenellaceae were further affected in these mice. This is the first report describing molecular responses in the colon and liver of Il10-/- mice fed a salmon diet associated with reduced colitis. Ultimately these responses could be validated for use in humans, and potentially enable management of IBD with diet.
Keywords: Colitis; Nutritional aspects; Omega-3 fatty acids